2007
DOI: 10.1093/nar/gkm956
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Information Network: the zebrafish model organism database provides expanded support for genotypes and phenotypes

Abstract: The Zebrafish Information Network (ZFIN, http://zfin.org), the model organism database for zebrafish, provides the central location for curated zebrafish genetic, genomic and developmental data. Extensive data integration of mutant phenotypes, genes, expression patterns, sequences, genetic markers, morpholinos, map positions, publications and community resources facilitates the use of the zebrafish as a model for studying gene function, development, behavior and disease. Access to ZFIN data is provided via web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 8 publications
(9 reference statements)
1
125
0
Order By: Relevance
“…Zebrafish have surged in importance as an animal model in almost every field of medicine, [9][10][11] owing to their publicly available genomic sequence, 12 their external fertilization, rapid development, accessibility of embryos (larvae) and the evolutionary conservation of the vertebrate body plan. Their precocious development of vision and remarkable evolutionary conservation of the eye make the zebrafish retina an excellent model for human visual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish have surged in importance as an animal model in almost every field of medicine, [9][10][11] owing to their publicly available genomic sequence, 12 their external fertilization, rapid development, accessibility of embryos (larvae) and the evolutionary conservation of the vertebrate body plan. Their precocious development of vision and remarkable evolutionary conservation of the eye make the zebrafish retina an excellent model for human visual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Robu et al (56) have proposed that an increase in p53-dependent cell death is an off-target nonspecific effect of some MOs, and they showed that it can be rescued by co-injection of a p53-MO of the same sequence. Using a MO to empty spiracles homeobox 3 (emx3-MO), which targets a transcription factor important for brain development (57) and has been previously shown to induce such nonspecific cell death, 4 we saw similar levels of acridine orange staining as in surf1-MO-injected fish. As previously observed by our colleagues, co-injection of the same p53-MO with emx3-MO ameliorated the apoptosis detectable with acridine orange staining in a dose-dependent manner.…”
Section: Reduction Of Either Coxva or Surf1mentioning
confidence: 82%
“…The E+Q approach is referred to as 'postcomposition' , reflecting the composition of compound terms from components. It is used in the EuroPhenome mouse phenotype database (www.europhenome.org/) to describe raw phenotype data from highthroughput phenotyping experiments (Beck et al, 2009;Morgan et al, 2010), and in some model organism databases such as ZFIN and FlyBase (Drysdale, 2008;Sprague et al, 2008). For example, to describe the phenotype of Sox9 mutants, MGI uses the pre-composed term MP:0005587 (abnormal Meckel's cartilage) and ZFIN uses the E+Q approach -entity, ZFA:0001205 (Meckel's cartilage); quality, PATO:000587 (decreased size).…”
Section: Special Articlementioning
confidence: 99%